Brief Report: CD4+ T Cells From Patients With Systemic Lupus Erythematosus Respond Poorly to Exogenous Interleukin‐2. Issue 4 (29th March 2017) - Comte, Denis; Karampetsou, Maria P.; Kis‐Toth, Katalin; Yoshida, Nobuya; Bradley, Sean J.; Kyttaris, Vasileios C.; Tsokos, George C.
Abstract : Objective: Imbalanced cytokine production by T cells characterizes both patients with systemic lupus erythematosus (SLE) and lupus‐prone mice and contributes to immune dysregulation. This study was undertaken to further investigate in detail the production of interleukin‐2 (IL‐2), interferon‐γ (IFNγ), IL‐4, and IL‐17A by CD4+ cell subsets in healthy subjects and patients with SLE, and the signaling response of CD4+ T cells in response to exogenous IL‐2. Methods: Cytokine production by differentiated subsets of CD4+ T cells was assessed by intracellular staining following stimulation with phorbol myristate acetate and ionomycin and by enzyme‐linked immunosorbent assay after anti‐CD3/anti‐CD28 stimulation. The IL‐2 signaling pathway was examined by assessing JAK‐3/STAT‐5 phosphorylation. Cell proliferation in response to IL‐2 was examined by carboxyfluorescein succinimidyl ester dilution. Results: Production of IL‐2 was defective primarily among naive CD4+ T cells, whereas the production of IFNγ, IL‐4, and IL‐17A was not significantly different between patients with SLE and healthy subjects. JAK‐3/STAT‐5 phosphorylation and proliferation of CD4+ T cells from SLE patients in response to exogenous IL‐2 were impaired compared to cells from healthy subjects. Conclusion: These data suggest that altered IL‐2 production, as well as impaired IL‐2–mediated signaling and proliferative responses, characterize SLE CD4+ T cells. Our data demonstrate the need for caution in designing IL‐2 treatment trials for patients with SLE. Approaches to restore CD4+ T cell sensitivity to IL‐2 should be considered.